The purpose of humanist formation at the University of Costa Rica of the 21st century - Monge Ortiz, Jorge Alberto (2020)
This article raises the need of the humanities in the professional training of the student who enters the University of Costa Rica in order to rescue a comprehensive vision that assists in the ethical insertion of the graduate of higher education.